First person - Monika J. Tomecka (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Monika Tomecka is first author on 'Clinical pathologies of bone fracture modelled in zebrafish', published in DMM. Monika conducted the research described in this article while a PhD student in Tom Carney's lab at the Institute of Molecular and Cell Biology (IMCB), A*STAR (Agency for Science, Technology and Research), Singapore and Henry Roehl's lab, Department of Biomedical Science, The University of Sheffield, UK. She is now a CEO at uFraction8, an engineering company that develops biotech instruments for industrial cell culture harvesting.